The High Coverage of Dental, Vision, and Hearing Benefits Among Medicare Advantage Enrollees - Amber Willink PhD (SAGE Publishing, 2019)
While the traditional Medicare program does not cover dental, vision, and hearing services, Medicare Advantage (MA) plans have been given the flexibility to do so. However, it is not known how many MA enrollees are in plans that cover these services. The 2016 Medicare Current Beneficiary Survey linked to MA plan benefit data is used to examine enrollment levels in plans that cover dental, vision, and/or hearing services in MA. Medicaid beneficiaries are excluded from this analysis as coverage of supplemental benefits is largely determined by the state. The highest coverage of supplemental services is vision, followed by hearing and dental (71%, 56%, and 41%, respectively). Across all supplemental services, coverage for supplemental benefits is highest among low-income beneficiaries and those who have not completed high school. Hispanic Medicare beneficiaries had the highest enrollment in plans that offered a supplemental benefit, and white Medicare beneficiaries tended to have the lowest enrollment in these plans. Unlike in traditional Medicare, MA enrollees have access to health plans that offer supplemental benefits, including dental, vision, and/or hearing services. This analysis shows that enrollment in these plans is highest among low-income MA enrollees who may not have the means to purchase stand-alone insurance for these services in traditional Medicare. More analysis is warranted to examine the generosity of the coverage of these services in MA plans. However, for federal policy makers to consider offering supplemental coverage in traditional Medicare, the MA experience suggests this type of benefit would be valuable.